Investor attention and ESG performance: Lessons from China's manufacturing industry - Jiafeng Gu (Journal of Environmental Management, 2024)
In the context of the rapid growth of corporate green investment and the rapid dissemination of information brought about by Internet technology, it is important to explore the relationship between investor attention and corporate environmental responsibility. Unfortunately, an in-depth research on the relationship between investor attention and firms' environment, society, and governance (ESG) performance remains unexplored. The results show a mutual inhibition between investor attention and firms’ ESG performance. Each 1% increase in investor attention decreases ESG performance by 0.252%, while each 1% increase in ESG performance decreases investor attention by 2.296%. Thus, ESG performance dominates this mutual influence. Moreover, ESG performance positively affects ESG performance and investor attention of neighboring firms. Each 1% increase in ESG performance increases ESG performance and investor attention of neighboring firms by 0.371% and 0.983%, respectively. Investor attention negatively affects investor attention and ESG performance of neighboring firms. Each 1% increase in investor attention decreases ESG performance and investor attention of neighboring firms by 0.04% and 0.104%, respectively. Further research reveals significant regional and organizational heterogeneity in the relationship between investor attention and ESG performance. The findings provide theoretical and empirical insights for further improvement of the ESG system and continued strengthening of investor guidance by regulators.